Evaluation of Compensatory Growth of 200 lb Finishing Pigs Previously Fed a Low Lysine Diet - Z. X. Rao; J. T. Gebhardt; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey; Robert D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 346 pigs (241 × 600, DNA, Columbus, NE; initially 195.3 lb) were used in a 44-d trial to evaluate the compensatory growth of 200 lb finishing pigs previously fed a low lysine diet. Two diets were manufactured (control and corn diet) and arranged into 4 nutritional strategies. One group of pigs (control) was fed the control diet from d 0 to 44. The other three groups of pigs were fed the corn diet for 2, 3, or 4 weeks and then switched to the control diet until d 44. The control diet contained 13.0% crude protein (CP) and 0.70% standardized ileal digestible (SID) Lys. The corn diet contained 8.1% CP and 0.18% SID Lys. There were 9 to 10 pigs per pen and 9 pens per treatment. On average, pigs fed the corn diet grew 49% slower per day than those on the control treatment. The first week after the dietary switch from corn to control diet (recovery period), pigs previously fed the corn diet grew approximately 28% faster than those fed the control treatment, then had approximately 12% greater average daily gain (ADG) than those fed the control treatment for the rest of the recovery period. Despite this compensatory increase in ADG, final body weight (BW) was still lower compared to control pigs, with the exception of the pigs that were only fed the corn diet for 2 weeks and then followed with 4 weeks of recovery on the control diet. Weekly average daily feed intake (ADFI) was similar to the control treatment when pigs were fed the corn diet, but like ADG, was greater during the first week of recovery then returned to similar levels as the control treatment. Weekly feed efficiency (F/G) was worse when pigs were fed the corn diet compared to the control treatment, but improved compared to those on the control treatment during the first week of recovery then returned to a similar level as the control treatment. For the overall period (d 0 to 44), control pigs and pigs fed the corn diet for the first 2 of the 6 weeks had increased (P<0.05) ADG compared to pigs fed the corn diet for the first 3 or 4 of the 6 weeks. Feed efficiency worsened (P<0.05) as the length of time that pigs were fed the corn diet increased. Pigs fed the corn diet for the first 3 or 4 weeks had increased (P<0.05) backfat and decreased (P<0.05) loin depth compared to pigs fed the control diet. These data suggest that feeding pigs the corn diet for the first 3 or 4 weeks followed by the control diet within a 6-week-period prior to marketing reduced the growth performance and carcass characteristics compared to pigs fed the control diet the entire time. These results allow producers to estimate the reduction in growth rate when feeding a low lysine corn-based diet and to estimate the recovery time when switching back to a control diet. This study provides insight into compensatory gain responses to dietary amino acid deficiencies.
Keywords: Compensatory growth; finishing pig; growth rate; late finishing; lysine